Factores clave para el proceso de gestión de la innovación para el desarrollo de nuevos productos en el sector PyMEs, caso de estudio la industria de tecnologías de la información en Nuevo León (Key factors for the process innovation management for new product development in the SME sector, case study information technology in Nuevo León) - López Treviño, Oscar Enrique; Blanco Jiménez, Mónica (Facultad de Contaduría Pública y Administración U.A.N.L., 2010)
Abstract. The purpose of this study is to analyze the key factors for managing the product innovation process, from existing models over time. Different proposals are presented by different authors who have studied this phenomenon, and as a result of these have conceptualized the knowledge in different models of innovation, so this work focuses on meeting certain elements in a new model including a new variable was not been considered in previous models (Organizational Creativity). This study was focused on SMEs and their importance in the economy of any country. The analysis of results and findings are presented from a study of 53 samples to the industry of information technology in Nuevo León, México.